2020
DOI: 10.3946/kjme.2020.180
|View full text |Cite
|
Sign up to set email alerts
|

Stereotypes among health professions in Indonesia: an explorative study

Abstract: Purpose: Effective and efficient health services require efforts to increase collaboration among health professionals. One of the barriers to effective collaboration is stereotypes. Stereotypes represent perceptions or perspectives about a person or group of people. This study aims to explore the perceptions of health professional students and practitioners regarding stereotypes. Methods: This was a qualitative study using a phenomenology approach. A sample of health professions students from both preclinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 26 publications
0
6
0
2
Order By: Relevance
“…Therefore, it fostered self-confidence in students. Students with high academic perceptions might have managed to make arrangements in terms of independent learning abilities because they believe they can do a job successfully, which can then be referred into a form of motivation (39)(40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it fostered self-confidence in students. Students with high academic perceptions might have managed to make arrangements in terms of independent learning abilities because they believe they can do a job successfully, which can then be referred into a form of motivation (39)(40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the literature suggests that incompetence stereotypes may impact the effectiveness of work interactions. For example, Darmayani et al (2020) interviewed 71 health professionals on the implications of stereotypes on effective collaboration and the quality of care. Findings suggested that incompetence stereotypes may inhibit communication between team members.…”
Section: The Social Identity Approach and Social Capital Theoriesmentioning
confidence: 99%
“…Findings suggested that incompetence stereotypes may inhibit communication between team members. In fact, participants perceived stereotypes as a barrier to effective collaboration in the workplace (Darmayani et al, 2020). Furthermore, findings from an experimental study in business situations showed that perceptions of competence acted as an indicator of the negotiator’s ability to provide instrumental support and significantly affected participants’ decision to collaborate with the negotiator (Zhang et al, 2021).…”
Section: The Social Identity Approach and Social Capital Theoriesmentioning
confidence: 99%
“…6 Faktor yang dapat menghambat komunikasi dan kinerja tim interprofesi adalah persepsi negatif terhadap profesi lain. 7 Persepsi meliputi kegiatan penerimaan, pengorganisasian, dan proses interpretasi terhadap stimulus. Persepsi mengenai IPE berhubungan dengan segala asumsi seseorang terhadap IPE yang mempengaruhi sikap dan perilaku seseorang terhadap IPE.…”
Section: Pendahuluanunclassified